PERAN KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI DAN KEPUASAN KERJA ( Studi Pada Dinas Pertanian dan KehutananKabupaten Rembang ) - Miske Sri Ariyani, 1142020027 (Students Journal of Economic and Management, 2013)
Human resources management is the planning, organizing, directing, and monitoring the activities of procurement, development compensation, integration, maintenance, and release of human resources in order to achieve various goals of individuals, organizations and communities. This phenomenon happens, that employees of the Department of Agriculture and Forestry District Rembang still assume that the work is done in the routine of everyday life so that no morale and motivation. In addition, many employees who work not optimal due to dissatisfaction with the workplace, occupation and employer. In this study, the population is all employees in the Department of Agriculture and Forestry District Rembang as many as 110 employees. Sampling is to be respondents in this study is using the census, where every member of the population as a whole serve as a sample. The number of respondents who were sampled as many as 110 employees in the Department of Agriculture and Forestry District Apex. Significance value of the test variable individual characteristics and job characteristics on performance through motivation and satisfaction suggests there is a hypothesis that rejected the job characteristics have a positive but not significant effect on satisfaction. The results also proved that the variable motivation and satisfaction does not mediate individual characteristic variables and job characteristics on employee performance Agriculture and Forestry District Apex. Keywords : Individual Characteristic, Job Characteristics, Motivation, Satisfaction, EmployeeÂ Â  Performance